(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
Early Triassic (Griesbachian to Spathian) ostracod faunas are here first discovered and described form the Guangxi Province, South China. Thirty-seven species belonging to fourteen genera are recognized. Seven species are new: Bairdia fengshanensis n.sp., Bairdia wailiensis n.sp., Liuzhinia guangxiensis n.sp., Ptychobairdia luciaae n.sp., Ptychobairdia aldaae n.sp., Paracypris jinyaensis n.sp. and Paracypris gaetanii n.sp. The Griesbachian assemblage from the basal microbial limestone is well diversified and does not suggest any abnormal palaeoenvironmental conditions in terms of salinity, temperature or oxygen content. Particularly, the ostracods are typical of well oxygenated water and do not reflect any anoxia. Dienerian and Smithian ostracods are evidenced for the first time and the assemblages suggest less favourable palaeoenviromental conditions. Diversity and abundance of ostracod assemblages recovered from the Spathian on. The main taxonomic turnover among ostracod assemblages occurred seemingly between the Griesbachian and the Spathian.